Analysis of piled raft behavior - Cheng, Yee Kiat. (2010)
The main objective of this project is to study the behavior of piled raft foundation system and analyze how piles are being designed optimally to control the displacements the foundation system. Piled raft foundation is different from the conventional pile foundation because engineers normally ignore the contribution of the raft and assume the loads are supported entirely by the piles. The piled raft foundation is more economical than the pile foundation because piles in the piled raft foundation do not have to penetrate the full depth of clay layer but can be terminated at higher elevations. However, the use of piled raft foundation system requires careful design and analysis as it involves complex pile-soil-structure interaction. Soil parameters are being input and finite element analyses were carried out to predict the deformation under working load conditions. Parametric studies are presented showing the effect of factors such as raft stiffness and pile lengths that influence the settlement and bending moment. In this project, design issues on piled raft foundation system will be discussed and compared to determine the factors that contribute in controlling settlement of the piled raft foundation system.